Artificial Intelligence-driven Cybersecurity Applications and Challenges - Bai, Zhaoyue; Miao, Hui; Miao, Junfeng; Xiao, Nan; Sun, Xiaoxue (Innovative Applications of AI, 2025)
In the era of big data, novel cyber attack methods are emerging endlessly. Traditional cybersecurity defense measures have become insufficient to counter these new threats, while the rapid development of artificial intelligence (AI) technology provides critical solutions for cybersecurity defense systems. The application of AI in the field of cybersecurity is primarily manifested in the following aspects. Firstly, intelligent threat monitoring and intrusion detection systems enable real-time indentification of anomalous behaviors. Secondly, machine learning-based automated defense and response mechanisms significantly enhance the efficiency of security incident handling. Thirdly, intelligent vulnerability and mining technologies greatly improve the capability to discover security flaws. Lastly, novel authentication technologies such as biometric recognition have reconstructed access control systems. However, the application of AI in cybersecurity still faces numerous challenges. The maturity of the technology needs further improvement and there is a severe shortage of interdisciplinary talent proficient in both AI and cybersecurity. The rapid evolution of attack methods increases defensive difficulties and the resulting ethical issues urgently require resolution. With the continuous advancement and refinement of technology, AI will undoubtedly build a more intelligent and efficient protective barrier for cebersecurity defense systems.